PENGARUH LITERASI KEUANGAN, INKLUSI KEUANGAN, DAN TINGKAT PENDAPATAN TERHADAP KEMAMPUAN PENGELOLAAN KEUANGAN PADA ASN DI KOTA SEMARANG - Lestari, Sri; Herry Subagyo; Retno Indah Hernawati (Universitas Dian Nuswantoro, 2025)
This study aims to examine the effect of financial literacy, financial inclusion, and income level on financial management ability among Civil Servants (ASN) in Semarang City, with gender as a comparrison. A quantitative survey method was applied to 374 randomly selected respondents. Data were analyzed using SEM-PLS to test validity, reliability, and relationships between latent constructs. The results reveal that financial literacy, financial inclusion, and income significantly and positively influence financial management ability. Among these factors, financial inclusion emerged as the most dominant determinant. Gender did not significantly moderate the relationships, although minor differences appeared between male and female respondents. These findings highlight the importance of enhancing access to formal financial services, strengthening financial literacy, and optimizing income to improve the financial stability of civil servants.